Carbon footprint and cost analysis of non-thermal food processing technologies: a review with a case study on orange juice - Yang, Minliang; Wang, Qingyang (Frontiers in Sustainable Food Systems, 2025)
Accelerating decarbonization in the food and beverage industry is critical to reducing greenhouse gas (GHG) emissions, as this sector accounts for approximately one-third of total emissions globally. Electrified, non-thermal food processing technologies offer promising alternatives to conventional thermal methods by improving energy efficiency and enabling cross-sectoral decarbonization. However, direct comparisons of their costs and environmental impacts remain limited due to the early-stage development of some technologies and variability in system configurations. This study provides a comprehensive review of four key non-thermal food processing technologies: high-pressure processing (HPP), pulsed electric fields (PEF), cold plasma, and ultraviolet light (UV). Using orange juice production as an illustrative case study, their industrial sustainability was evaluated through life cycle assessment (LCA) and technoeconomic analysis (TEA). Our LCA/TEA results show that, compared to conventional thermal pasteurization, orange juice processed with non-thermal technologies has slightly higher selling prices, with HPP being the most expensive. The carbon footprints of non-thermal processes are comparable to or lower than those of thermal pasteurization. This review offers valuable insights into the sustainability of various non-thermal food technologies, identifies key environmental and economic hotspots for industrial application, and serves as a guide for advancing sustainable practices in the food industry.